A novel deep autoencoder and hyperparametric adaptive learning for imbalance intelligent fault diagnosis of rotating machinery. (June 2021) - Li, Wanxiang; Shang, Zhiwu; Gao, Maosheng; Qian, Shiqi; Zhang, Baoren; Zhang, Jie
Highlights: The ORJ data augmentation strategy is designed to augmentation training samples. A deep SAE-LNC is proposed to improve the ability of capturing nonlinear features. Propose a hyperparameter adaptive learning method of deep neural network. Proposed method can capture high-quality state features and obtain higher diagnostic accuracy.